2004
DOI: 10.1152/ajplung.00287.2003
|View full text |Cite
|
Sign up to set email alerts
|

8-Bromo-cAMP decreases the Ca2+sensitivity of airway smooth muscle contraction through a mechanism distinct from inhibition of Rho-kinase

Abstract: Endou, Katsuaki, Kunihiko Iizuka, Akihiro Yoshii, Hideo Tsukagoshi, Tamotsu Ishizuka, Kunio Dobashi, Tsugio Nakazawa, and Masatomo Mori. 8-Bromo-cAMP decreases the Ca 2ϩ sensitivity of airway smooth muscle contraction through a mechanism distinct from inhibition of Rho-kinase. Am J Physiol Lung Cell Mol Physiol 287: L641-L648, 2004. First published April 30, 2004 10.1152/ajplung.00287.2003.-To clarify whether cyclic AMP (cAMP)/cAMP-dependent protein kinase (PKA) activation and Rhokinase inhibition share a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…All these cAMP‐related agents caused less reduction in [Ca 2+ ] i than SKF‐96365 when an equivalent relaxation was achieved (Figs 1–3), demonstrating that Ca 2+ ‐independent mechanisms are involved in cAMP‐dependent relaxation in ASM. This observation is consistent with previous reports [19, 20].…”
Section: Discussionsupporting
confidence: 94%
“…All these cAMP‐related agents caused less reduction in [Ca 2+ ] i than SKF‐96365 when an equivalent relaxation was achieved (Figs 1–3), demonstrating that Ca 2+ ‐independent mechanisms are involved in cAMP‐dependent relaxation in ASM. This observation is consistent with previous reports [19, 20].…”
Section: Discussionsupporting
confidence: 94%
“…Cardiac myocyte-specific overexpression of an active form of Rac predisposes the heart to postischemic contractile dysfunction (Talukder et al, 2013). Through activation of NADPH oxidase, Rac1 activation contributes to oxidative stress, which promotes cardiac injury and dysfunction (Maack et al, 2003;Endou et al, 2004;Elnakish et al, 2012;Nagase et al, 2012;Zhang et al, 2012;Ma et al, 2013). Moreover, Rac1 is essential for the hypertrophic response in the heart (Sussman et al, 2000;Satoh et al, 2006;Vettel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A similar relaxation of model airways was also observed in response to the cAMPelevating compounds, FSK and IBMX. This effect of cAMP may also act via the activation of MLCP because in previous studies, cAMP-dependent PKA (or cross-activated PKG) was reported to antagonize inhibitors of MLCP, including of RhoA, pre-RhoA signaling molecules (i.e., G␣ q or G␣ 12,13 ), and CPI-17 (12,26,37). Caffeine, presumably acting as a phosphodiesterase inhibitor to elevate cAMP, also served to relax the MCh-contracted airways but this effect required relatively high concentrations of caffeine compared with the effective concentrations of FSK or IBMX.…”
Section: Discussionmentioning
confidence: 99%